FACTORS INFLUENCE THE CONSUMER’S ONLINE SHOPPING BEHAVIOR ON COSMETIC AT PIZU LTD COMPANY - Thuy Dung, Nguyen; Thi Thu Nga, Nguyen (Journal of Forestry Science and Technology, 2020)
The purpose of this research is to investigate into what factors influence the consumer’s online shopping behavior on cosmetic. Nowaday, cosmestic are becoming more and more popular with so many brands, products in the markets, there has been a fierce competition among different cosmetic producers. Consumers have so many choices from luxury to common brands. Thanks to the growing convenience of e-commerce, consumers are now spared from store visiting and offline transaction... This study has been conducted based on the structured survey of 280 customers of Pizu Ltd Company, a 5 year-old cosmetic e-commerce business. The study results reveal that there are six factors that influence consumer’s behavior including: (1) Product; (2) Convenience; (3) Delivery; (4) Service and infrastructure; (5) Consumer attitude; (6) Shopping attitude, while financial and return policies are not clearly linked to consumer’s behavior. The six factors provide a useful initial framework for Pizu company to assess its current strategy and tactics. The research also suggests several approaches which Pizu company can undertake to better influence consumer’s behavior, thus, increasing its own online shopping revenue. These approaches includes increasing the quality of products, provide more product’s visuals and information on the website. Increasing the quality of service and infrastructure; quality of product; design website display more sightly, create photos and informations about product more abundantly.